Polyester composite fiber for dust cover and preparation method thereof
By using the leather core structure of silica-modified polyester slices and polyester slices, combined with the cross-linking reaction of thiolated silica and cis-2-butene-1,4-diol, the problems of poor hydrophobicity and low durability of the polyester fibers for dustproof covers are solved, and the dustproof cover fibers with superhydrophobic and high flush resistance are achieved.
Patent Information
- Application Number
- CN202411264089.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-09-10
AI Technical Summary
The existing polyester fibers for dustproof covers have poor hydrophobicity and low durability, making it difficult to effectively prevent dust from adhesion and cleaning.
Silica modified polyester slices are used as the cortical component and polyester slices are used as the core component. Through composite melt spinning technology, a 20:80 skin-core ratio structure is constructed, and the cross-linking reaction of thiolated silica and cis-2-butene-1,4-diol is used to improve the tensile and hydrophobic properties of the fibers.
The superhydrophobic surface and high flush resistance are achieved, which significantly improves dust resistance, reduces dry heat shrinkage, and enhances the durability of the fiber.
Smart Images

Figure BDA0005036642510000111
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite polyester, and in particular to a polyester composite fiber for a dust cover and a preparation method thereof. Background Art
[0002] Polyester fiber has become the most widely used and consumed fiber variety due to its advantages such as high modulus, high strength, high elasticity, good shape retention and heat resistance. It is widely used in textile and clothing manufacturing, bringing a lot of convenience and comfort to our daily life. In the field of dust cover preparation technology, polyester fiber is also an extremely important raw material.
[0003] As people's demands for quality of life become higher and higher, the quality and function of dust covers are also put forward higher and higher requirements. However, textiles made of polyester fibers have poor hydrophobicity. After encountering water, they not only wet themselves, but also make dust adhere more tightly to the surface of textiles, making them difficult to clean.
[0004] Chinese invention patent CN 103469356B relates to a method for preparing a sheath-core composite fiber with poly(ethylene terephthalate) (PET) as the sheath material and PET as the core material. Although the polyester fiber prepared by this method has a good hydrophobic effect, the raw material fluoroterephthalic acid used in this method is difficult to obtain and cannot be industrialized. Summary of the invention
[0005] In view of this, the purpose of the present invention is to provide a polyester composite fiber for dust covers and a preparation method thereof, so as to solve the problems of poor hydrophobicity and low durability of the current polyester fibers for dust covers.
[0006] Based on the above purpose, the present invention provides a polyester composite fiber for a dust cover, wherein the polyester composite fiber has silica-modified polyester chips as the skin component and polyester chips as the core component, and is obtained by composite melt spinning at a skin-core ratio of 20:80.
[0007] Further, the preparation method of the silica-modified polyester chips is as follows:
[0008] S1: In a nitrogen atmosphere, terephthalic acid, isophthalic acid, 1,4-butanediol, and cis-2-butene-1,4-diol are added to a reactor, and then a catalyst is added. The temperature is raised to 230-250°C, and the reaction is carried out at normal pressure for 3-5 hours. The pressure is then reduced to 0.02-0.08MPa, and the reaction is carried out for 30-50 minutes. The pressure is then reduced to 40-60Pa, and the temperature is controlled to be 240-260°C. The reaction is stirred for 1.5-3 hours, and the vacuum system is closed. The nitrogen is filled to increase the pressure, and the polymer is extruded. The polymer is cooled in a water tank, and sliced by a pelletizer to obtain unsaturated polyester slices.
[0009] S2: adding unsaturated polyester chips, mercapto-modified silica powder and photoinitiator into a stirring kettle, heating to 230-250° C., irradiating under a 300W ultraviolet lamp for reaction for 50-70 minutes during stirring, cooling in a water tank, and cutting into chips by a pelletizer to obtain silica-modified polyester chips;
[0010] Preferably, in step S1, the molar ratio of terephthalic acid, isophthalic acid, 1,4-butanediol and cis-2-butene-1,4-diol is 1:0.05-0.2:1:0.3-0.5.
[0011] Preferably, the catalyst in step S1 is antimony trioxide, and the added amount is 0.01%-0.03% of the weight of terephthalic acid.
[0012] Preferably, in step S2, the weight ratio of the unsaturated polyester chips to the mercapto-modified silica powder is 20:3-5.
[0013] Preferably, the photoinitiator in step S2 is 2,2-dimethoxy-2-phenylacetophenone, and the added amount is 0.01%-0.03% of the weight of the unsaturated polyester chips.
[0014] Preferably, the preparation method of the mercapto-modified silica powder in step S2 is as follows: adding silica powder to a mixed solution of ethanol and deionized water, adjusting the pH to 4 with hydrochloric acid, ultrasonically dispersing for 5-20 minutes, then adding silane coupling agent KH-590, heating to 55-65° C., stirring for reaction for 10-14 hours, centrifuging, washing with alcohol 2-3 times, and vacuum drying to obtain mercapto-modified silica powder.
[0015] Preferably, the particle size of the silicon dioxide powder is 400-600 nm.
[0016] Preferably, the weight ratio of the silicon dioxide powder, ethanol, deionized water and silane coupling agent KH-590 is 1:60:20:0.1.
[0017] Furthermore, the present invention also provides a method for preparing polyester composite fibers for dust covers, comprising the following steps: extruding and melting the skin layer components and the core layer components into melts in respective screw extruders, wherein the temperatures of the skin layer screw extruders are 230±5°C, 265±5°C, 265±5°C, and 265±5°C, and the temperatures of the core layer screw extruders are 260±5°C, 290±5°C, 298±5°C, and 298±5°C, and the ratio of the two components is adjusted by a metering pump, and the skin-core ratio is 20:80. After composite melt spinning, the box temperature is 300±5°C, the spinning speed is 2000m / min, bundling, 1.4-2 times drafting, and heat setting at 100±5°C to obtain polyester composite fibers for dust covers.
[0018] Beneficial effects of the present invention:
[0019] The present invention adopts mercapto silicon dioxide powder to modify unsaturated polyester. The mercapto silicon dioxide is cross-linked in the unsaturated polyester through a mercapto-ene click reaction, thereby improving the tensile properties and reducing the melting point of the silicon dioxide-modified polyester slices, and achieving a lower dry heat shrinkage rate. The silicon dioxide is used as a skin layer and polyester to construct a polyester composite fiber with a skin-core structure. After weaving and heat treatment, a super-hydrophobic surface and high erosion resistance are achieved, and the dustproof ability is effectively improved.
[0020] The present invention adopts cis-2-butene-1,4-diol as a raw material to construct unsaturated polyester. Cis-2-butene-1,4-diol adjusts the melting point of silica-modified polyester slices on the one hand, and provides cross-linking sites on the other hand, so that mercapto silica can be cross-linked in the polyester main chain. In addition, the cross-linking sites of the polyester main chain are controlled, so that mercapto silica is cross-linked in the non-crystalline region, which is conducive to the construction of a super-hydrophobic structure. DETAILED DESCRIPTION
[0021] In order to make the purpose, technical scheme and advantages of the present invention more clear, the present invention is further described in detail below in conjunction with specific embodiments. The present invention provides these embodiments to make the present invention thorough and complete, and to fully express the scope of the present invention to those skilled in the art. It should be noted that unless otherwise specifically stated, the relative arrangement of the parts and steps, the composition of the materials, the numerical expressions and the numerical values described in these embodiments should be interpreted as merely exemplary, rather than as limiting.
[0022] In a specific embodiment of the present invention, the particle size of the silicon dioxide powder is 500 nm.
[0023] Embodiment 1:
[0024] (1) Add 1 g of silica powder to a mixed solution of 60 g of ethanol and 20 g of deionized water, adjust the pH to 4 with hydrochloric acid, perform ultrasonic dispersion for 10 min, then add 0.1 g of silane coupling agent KH-590, heat to 60° C., stir and react for 12 h, centrifuge, wash with alcohol 3 times, and vacuum dry to obtain mercapto-modified silica powder;
[0025] (2) In a nitrogen atmosphere, 16.61 g of terephthalic acid, 1.66 g of isophthalic acid, 9.01 g of 1,4-butanediol, and 3.52 g of cis-2-butene-1,4-diol were added to a reaction kettle, and then 30 mg of antimony trioxide was added. The temperature was raised to 240° C., and the reaction was carried out at normal pressure for 4 h. The pressure was then reduced to 0.05 MPa, and the reaction was carried out for 40 min. The pressure was then reduced to 50 Pa, and the temperature was controlled to 250° C. The reaction was stirred for 2 h, and the vacuum system was closed. The nitrogen was filled to increase the pressure, and the polymer was extruded. The polymer was cooled in a water tank and sliced by a pelletizer to obtain unsaturated polyester slices.
[0026] (3) 20 g of unsaturated polyester chips, 5 g of mercapto-modified silica powder and 20 mg of 2,2-dimethoxy-2-phenylacetophenone were added to a stirring kettle, the temperature was raised to 240° C., and during the stirring process, the mixture was irradiated under a 300 W ultraviolet lamp for reaction for 60 min. The mixture was cooled in a water tank and sliced by a pelletizer to obtain silica-modified polyester chips.
[0027] (4) The silica-modified polyester chips are used as the skin component and the polyester chips are used as the core component. The skin component and the core component are extruded and melted into a melt in respective screw extruders. The temperatures of the skin layer screw extruder are 230°C, 265°C, 265°C, and 265°C, and the temperatures of the core layer screw extruder are 260°C, 290°C, 298°C, and 298°C. The ratio of the two components is adjusted by a metering pump. The skin-core ratio is 20:80. After composite melt spinning, the box temperature is 300°C, the spinning speed is 2000m / min, bundling, 1.6 times drafting, and heat setting at 100°C, a polyester composite fiber for dust cover with a linear density of 43.5dtex is obtained.
[0028] Embodiment 2:
[0029] (1) Add 1 g of silica powder to a mixed solution of 60 g of ethanol and 20 g of deionized water, adjust the pH to 4 with hydrochloric acid, perform ultrasonic dispersion for 10 min, then add 0.1 g of silane coupling agent KH-590, heat to 60° C., stir and react for 12 h, centrifuge, wash with alcohol 3 times, and vacuum dry to obtain mercapto-modified silica powder;
[0030] (2) In a nitrogen atmosphere, 16.61 g of terephthalic acid, 0.83 g of isophthalic acid, 9.01 g of 1,4-butanediol, and 2.64 g of cis-2-butene-1,4-diol were added to a reaction kettle, and then 16.6 mg of antimony trioxide was added. The temperature was raised to 230° C., and the reaction was carried out at normal pressure for 3 h. The pressure was then reduced to 0.02 MPa, and the reaction was carried out for 30 min. The pressure was then reduced to 40 Pa, and the temperature was controlled to 240° C. The reaction was stirred for 1.5 h, and the vacuum system was closed. The system was pressurized with nitrogen to extrude the polymer, which was cooled in a water tank and sliced by a pelletizer to obtain unsaturated polyester slices.
[0031] (3) 20 g of unsaturated polyester chips, 3 g of mercapto-modified silica powder and 20 mg of 2,2-dimethoxy-2-phenylacetophenone were added to a stirring kettle, the temperature was raised to 240° C., and during the stirring process, the mixture was irradiated under a 300 W ultraviolet lamp for reaction for 50 min. The mixture was cooled in a water tank and sliced by a pelletizer to obtain silica-modified polyester chips.
[0032] (4) The silica-modified polyester chips are used as the skin component and the polyester chips are used as the core component. The skin component and the core component are extruded and melted into a melt in respective screw extruders. The temperatures of the skin layer screw extruder are 230°C, 265°C, 265°C, and 265°C, and the temperatures of the core layer screw extruder are 260°C, 290°C, 298°C, and 298°C. The ratio of the two components is adjusted by a metering pump. The skin-core ratio is 20:80. After composite melt spinning, the box temperature is 300°C, the spinning speed is 2000m / min, bundling, 1.4 times drafting, and heat setting at 100°C, a polyester composite fiber for dust cover with a linear density of 46.5dtex is obtained.
[0033] Embodiment 3:
[0034] (1) Add 1 g of silica powder to a mixed solution of 60 g of ethanol and 20 g of deionized water, adjust the pH to 4 with hydrochloric acid, perform ultrasonic dispersion for 10 min, then add 0.1 g of silane coupling agent KH-590, heat to 60° C., stir and react for 12 h, centrifuge, wash with alcohol 3 times, and vacuum dry to obtain mercapto-modified silica powder;
[0035] (2) In a nitrogen atmosphere, 16.61 g of terephthalic acid, 3.32 g of isophthalic acid, 9.01 g of 1,4-butanediol, and 4.4 g of cis-2-butene-1,4-diol were added to a reaction kettle, and then 49 mg of antimony trioxide was added. The temperature was raised to 250° C., and the reaction was carried out at normal pressure for 5 h. The pressure was then reduced to 0.08 MPa, and the reaction was carried out for 50 min. The pressure was then reduced to 60 Pa, and the temperature was controlled to 260° C. The reaction was stirred for 3 h, and the vacuum system was closed. The system was pressurized with nitrogen to extrude the polymer, which was cooled in a water tank and sliced by a pelletizer to obtain unsaturated polyester slices.
[0036] (3) 20 g of unsaturated polyester chips, 5 g of mercapto-modified silica powder and 20 mg of 2,2-dimethoxy-2-phenylacetophenone were added to a stirring kettle, the temperature was raised to 250° C., and during the stirring process, the mixture was irradiated under a 300 W ultraviolet lamp for reaction for 70 min. The mixture was cooled in a water tank and sliced by a pelletizer to obtain silica-modified polyester chips.
[0037] (4) The silica-modified polyester chips are used as the skin component and the polyester chips are used as the core component. The skin component and the core component are extruded and melted into a melt in respective screw extruders. The temperatures of the skin layer screw extruder are 230°C, 265°C, 265°C, and 265°C, and the temperatures of the core layer screw extruder are 260°C, 290°C, 298°C, and 298°C. The ratio of the two components is adjusted by a metering pump. The skin-core ratio is 20:80. After composite melt spinning, the box temperature is 300°C, the spinning speed is 2000m / min, bundling, 12-fold drafting, and heat setting at 100°C, a polyester composite fiber for dust cover with a linear density of 38.2dtex is obtained.
[0038] Comparative Example 1:
[0039] The difference between Comparative Example 1 and Example 1 is that no mercapto modification is performed, and the silicon dioxide powder is directly added to the skin layer raw material. The specific steps are as follows;
[0040] (1) In a nitrogen atmosphere, 16.61 g of terephthalic acid, 1.66 g of isophthalic acid, 9.01 g of 1,4-butanediol, and 3.52 g of cis-2-butene-1,4-diol were added to a reaction kettle, and then 30 mg of antimony trioxide was added. The temperature was raised to 240° C., and the reaction was carried out at normal pressure for 4 h. The pressure was then reduced to 0.05 MPa, and the reaction was carried out for 40 min. The pressure was then reduced to 50 Pa, and the temperature was controlled to 250° C. The reaction was stirred for 2 h, and the vacuum system was closed. The system was pressurized with nitrogen to extrude the polymer, which was cooled in a water tank and sliced by a pelletizer to obtain unsaturated polyester slices.
[0041] (2) 20 g of unsaturated polyester chips, 4 g of silica powder and 20 mg of 2,2-dimethoxy-2-phenylacetophenone were added to a stirring kettle, the temperature was raised to 240° C., and during the stirring process, the mixture was irradiated under a 300 W ultraviolet lamp for reaction for 60 min. The mixture was cooled in a water tank and sliced by a pelletizer to obtain silica-modified polyester chips.
[0042] (3) The silica-modified polyester chips are used as the skin layer and the polyester chips are used as the core layer. The skin layer components and the core layer components are extruded and melted into melts in respective screw extruders. The temperatures of the skin layer screw extruders are 230, 265, 265, and 265, and the temperatures of the core layer screw extruders are 260, 290, 298, and 298. The ratio of the two components is adjusted by a metering pump. The skin-core ratio is 20:80. After composite melt spinning, the box temperature is 300°C, the spinning speed is 2000m / min, bundling, 1.6 times drafting, and heat setting at 100°C, a polyester composite fiber for dust cover with a linear density of 42.5dtex is obtained.
[0043] Comparative Example 2:
[0044] The difference between Comparative Example 2 and Example 1 is that cis-2-butene-1,4-diol is not added to the raw materials for preparing the unsaturated polyester chips. The specific steps are as follows:
[0045] (1) Add 1 g of silica powder to a mixed solution of 60 g of ethanol and 20 g of deionized water, adjust the pH to 4 with hydrochloric acid, perform ultrasonic dispersion for 10 min, then add 0.1 g of silane coupling agent KH-590, heat to 60° C., stir and react for 12 h, centrifuge, wash with alcohol 3 times, and vacuum dry to obtain mercapto-modified silica powder;
[0046] (2) In a nitrogen atmosphere, 16.61 g of terephthalic acid, 1.66 g of isophthalic acid, and 12.61 g of 1,4-butanediol were added to a reactor, and then 30 mg of antimony trioxide was added. The temperature was raised to 240° C., and the reaction was carried out at normal pressure for 4 h. The pressure was then reduced to 0.05 MPa, and the reaction was carried out for 40 min. The pressure was then reduced to 50 Pa, and the temperature was controlled to 250° C. The reaction was stirred for 2 h, and the vacuum system was closed. The system was filled with nitrogen to increase the pressure, and the polymer was extruded. The polymer was cooled in a water tank and sliced by a pelletizer to obtain polyester slices.
[0047] (3) 20 g of polyester chips, 4 g of mercapto-modified silica powder and 20 mg of 2,2-dimethoxy-2-phenylacetophenone were added to a stirring kettle, the temperature was raised to 240° C., and during the stirring process, the mixture was irradiated under a 300 W ultraviolet lamp for 60 min. The mixture was cooled in a water tank and sliced by a pelletizer to obtain silica-modified polyester chips.
[0048] (4) The silica-modified polyester chips are used as the skin layer and the polyester chips are used as the core layer. The skin layer components and the core layer components are extruded and melted into a melt in respective screw extruders. The temperatures of the skin layer screw extruders are 230, 265, 265, and 265, and the temperatures of the core layer screw extruders are 260, 290, 298, and 298. The ratio of the two components is adjusted by a metering pump. The skin-core ratio is 20:80. After composite melt spinning, the box temperature is 300°C, the spinning speed is 2000m / min, bundling, 1.6 times drafting, and heat setting at 100°C, a polyester composite fiber for dust cover with a linear density of 43.2dtex is obtained.
[0049] Comparative Example 3:
[0050] The difference between Comparative Example 3 and Example 1 is that isophthalic acid is not added to the raw materials for preparing the unsaturated polyester chips, and the specific steps are as follows:
[0051] (1) Add 1 g of silica powder to a mixed solution of 60 g of ethanol and 20 g of deionized water, adjust the pH to 4 with hydrochloric acid, perform ultrasonic dispersion for 10 min, then add 0.1 g of silane coupling agent KH-590, heat to 60° C., stir and react for 12 h, centrifuge, wash with alcohol 3 times, and vacuum dry to obtain mercapto-modified silica powder;
[0052] (2) In a nitrogen atmosphere, 18.27 g of terephthalic acid, 9.01 g of 1,4-butanediol, and 3.52 g of cis-2-butene-1,4-diol were added to a reaction kettle, and then 30 mg of antimony trioxide was added. The temperature was raised to 240° C., and the reaction was carried out at normal pressure for 4 h. The pressure was then reduced to 0.05 MPa, and the reaction was carried out for 40 min. The pressure was then reduced to 50 Pa, and the temperature was controlled to 250° C. The reaction was stirred for 2 h, and the vacuum system was closed. The nitrogen was filled to increase the pressure, and the polymer was extruded. The polymer was cooled in a water tank and sliced by a pelletizer to obtain unsaturated polyester slices.
[0053] (3) 20 g of unsaturated polyester chips, 4 g of mercapto-modified silica powder and 20 mg of 2,2-dimethoxy-2-phenylacetophenone were added to a stirring kettle, the temperature was raised to 240° C., and during the stirring process, the mixture was irradiated under a 300 W ultraviolet lamp for reaction for 60 min. The mixture was cooled in a water tank and sliced by a pelletizer to obtain silica-modified polyester chips.
[0054] (4) The silica-modified polyester chips are used as the skin layer and the polyester chips are used as the core layer. The skin layer components and the core layer components are extruded and melted into melts in respective screw extruders. The temperatures of the skin layer screw extruders are 230, 265, 265, and 265, and the temperatures of the core layer screw extruders are 260, 290, 298, and 298. The ratio of the two components is adjusted by a metering pump. The skin-core ratio is 20:80. After composite melt spinning, the box temperature is 300°C, the spinning speed is 2000m / min, bundling, 1.6 times drafting, and heat setting at 100°C, a polyester composite fiber for dust cover with a linear density of 42.8dtex is obtained.
[0055] Comparative Example 4:
[0056] The difference between Comparative Example 4 and Example 1 is that the polyester fiber is directly prepared, and the specific steps are as follows;
[0057] The polyester chips were extruded and melted into a melt in a screw extruder, and the temperatures of each zone of the screw extruder were 260, 290, 298, and 298. After melt spinning, the box temperature was 300°C, the spinning speed was 2000m / min, bundling, 1.6 times drafting, and heat setting at 100°C, a polyester fiber with a linear density of 43.8dtex was obtained.
[0058] Performance Testing
[0059] Melting point: The melting points of the cortical layers prepared in the examples and comparative examples were tested using a binocular microscopic melting point tester.
[0060] Tensile properties: Referring to the national standard GB / T 14337, the tensile properties of staple fibers were measured using a fiber strength and elongation tester with a clamping distance of 20 mm, a tensile speed of 20 mm / min, and a pre-tension of 0.13 cN / dtex. The results are shown in Table 1.
[0061] Dry heat shrinkage: refer to GBT 6505-2001 "Test method for thermal shrinkage of synthetic filaments", treat the sample with dry hot air, measure the change in sample length before and after, calculate the dry heat shrinkage, the heat treatment temperature is 85℃, the heat treatment time is 15min, and the results are shown in Table 1.
[0062] Wettability: The fibers prepared in the examples and comparative examples were first opened five times using an opener, and then the opened samples were made into a fabric with a length of 20 cm, a width of 20 cm, and a thickness of 5 cm using a fiber carding machine. The water contact angle was tested using a contact angle meter, and then the fabric was heat treated at 210°C for 20 min. After cooling, the water contact angle was tested using a contact angle meter. The results are shown in Table 2.
[0063] Scour resistance: The sample surface was tested for wettability by water impact at an impact pressure of 50 KPa. The angle between the fabric and the water flow was 45°. Each impact lasted for 1 min, and the impact cycle was 200 times. After drying, the water contact angle was tested using a contact angle meter. The water contact angle of the sample surface without water impact was compared to evaluate the scour resistance. The results are shown in Table 2.
[0064] Table 1 Fiber performance test results
[0065] sample Melting point / ℃ <![CDATA[Breaking strength / cN·dtex -1 > Elongation at break / % Dry heat shrinkage / % Example 1 201.3 5.35 46.3 10.5 Example 2 209.4 5.02 52.6 12.1 Example 3 193.5 5.31 44.3 9.2 Comparative Example 1 211.4 5.01 51.5 15.2 Comparative Example 2 213.5 4.85 53.2 16.4 Comparative Example 3 235.6 5.62 41.6 8.4 Comparative Example 4 268.5 6.52 35.2 5.4
[0066] Data Analysis:
[0067] It can be seen from Examples 1-3 that the polyester composite fiber for dust cover prepared by the present invention has good tensile properties, and its breaking strength can reach 5.35 cN·dtex -1 Most importantly, it has a low dry heat shrinkage rate, which realizes the low melting point cortical structure while avoiding the high dry heat shrinkage rate caused by the low crystallinity of the low melting point cortical structure.
[0068] It can be seen from Example 1 and Comparative Example 1 that directly adding silica powder to the cortex raw material will lead to a decrease in the tensile properties of the fiber. This is mainly because the silica powder affects the crystallization of the cortex on the one hand, and on the other hand, the silica powder agglomerates in the cortex, thereby reducing the tensile properties of the fiber.
[0069] It can be seen from Example 1 and Comparative Example 2 that cis-2-butene-1,4-diol helps to improve the tensile properties. This is mainly because cis-2-butene-1,4-diol improves the dispersion of silica powder in the cortex, and the silica powder can also form cross-linking results in the cortex through cis-2-butene-1,4-diol.
[0070] Table 2 Fabric performance test results
[0071]
[0072] Data Analysis:
[0073] It can be seen from Examples 1-3 and Comparative Example 4 that the fabric prepared with the polyester composite fiber for dust cover provided by the present invention has super hydrophobic properties, a water contact angle of up to 161.3°, and has high scouring resistance. After a long period of scouring, the water contact angle remains at 157.1°, showing only a small decrease. The super hydrophobic property prevents dust from adhering to the surface of the fabric, especially dust containing water vapor, and the super hydrophobic property also helps to remove dust by water washing. The water contact angle of the fabric prepared with traditional polyester fibers is only 86.1°, and dust containing water vapor easily adheres to its surface and is difficult to clean.
[0074] It can be seen from Example 1 and Comparative Examples 1-2 that mercapto silica and cis-2-butene-1,4-diol synergistically improve the hydrophobic properties of fabrics prepared from fibers. This is mainly because mercapto silica and cis-2-butene-1,4-diol allow silica to be grafted to the non-crystalline region in the polyester. After heat treatment, silica is arranged on the surface of the fabric under the action of internal stress, and the polyester in the cortex is further melted and solidified, so that silica presents a rough structure on the surface of the fabric, thereby constructing a super hydrophobic surface.
[0075] It can be seen from Example 1 and Comparative Example 3 that the use of isophthalic acid can further improve the hydrophobic property. This is because, on the one hand, isophthalic acid lowers the melting point of the cortex, so that more silica is exposed to the fabric surface during the heat treatment process. On the other hand, the larger steric hindrance of isophthalic acid promotes the arrangement of silica on the fabric surface.
[0076] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.
Claims
1. A polyester composite fiber for a dust cover, characterized in that: The polyester composite fiber is obtained by composite melt spinning with silica-modified polyester chips as the skin component and polyester chips as the core component at a skin-core ratio of 20:80; The preparation method of the silica-modified polyester chips is as follows: S1: In a nitrogen atmosphere, terephthalic acid, isophthalic acid, 1,4-butanediol, and cis-2-butene-1,4-diol are added to a reactor, and then a catalyst is added. The temperature is raised to 230-250°C, and the reaction is carried out at normal pressure for 3-5 hours. The pressure is then reduced to 0.02-0.08MPa, and the reaction is carried out for 30-50 minutes. The pressure is then reduced to 40-60Pa, and the temperature is controlled to be 240-260°C. The reaction is stirred for 1.5-3 hours, and the vacuum system is closed. The nitrogen is filled to increase the pressure, and the polymer is extruded. The polymer is cooled in a water tank, and sliced by a pelletizer to obtain unsaturated polyester slices. S2: adding unsaturated polyester chips, mercapto-modified silica powder and photoinitiator into a stirring kettle, heating to 230-250° C., irradiating under a 300W ultraviolet lamp for reaction for 50-70 minutes during stirring, cooling in a water tank, and cutting into chips by a pelletizer to obtain silica-modified polyester chips; In step S1, the molar ratio of terephthalic acid, isophthalic acid, 1,4-butanediol and cis-2-butene-1,4-diol is 1:0.05-0.2:1:0.3-0.5; In step S2, the weight ratio of the unsaturated polyester chips to the mercapto-modified silica powder is 20:3-5; The preparation method of the mercapto-modified silica powder in step S2 is as follows: adding silica powder to a mixed solution of ethanol and deionized water, adjusting the pH to 4 with hydrochloric acid, ultrasonically dispersing for 5-20 minutes, then adding silane coupling agent KH-590, heating to 55-65° C., stirring for reaction for 10-14 hours, centrifuging, washing with alcohol 2-3 times, and vacuum drying to obtain mercapto-modified silica powder.
2. The polyester composite fiber for dust cover according to claim 1, characterized in that: In step S1, the catalyst is antimony trioxide, and the added amount is 0.01%-0.03% of the weight of terephthalic acid.
3. The polyester composite fiber for dust cover according to claim 1, characterized in that: In step S2, the photoinitiator is 2,2-dimethoxy-2-phenylacetophenone, and the added amount is 0.01%-0.03% of the weight of the unsaturated polyester chips.
4. The polyester composite fiber for a dust cover according to claim 1, characterized in that: The particle size of the silicon dioxide powder is 400-600 nm.
5. The polyester composite fiber for a dust cover according to claim 1, characterized in that: The weight ratio of the silicon dioxide powder, ethanol, deionized water and silane coupling agent KH-590 is 1:60:20:0.
1.
6. A method for preparing the polyester composite fiber for a dust cover according to any one of claims 1 to 5, characterized in that: The method comprises the following steps: extruding and melting the skin layer component and the core layer component into melts in respective screw extruders, wherein the temperature of each section of the skin layer screw extruder is 230±5°C, 265±5°C, 265±5°C, and 265±5°C, and the temperature of each section of the core layer screw extruder is 260±5°C, 290±5°C, 298±5°C, and 298±5°C, adjusting the ratio of the two components by a metering pump, and the skin-core ratio is 20:80; and performing composite melt spinning with a box temperature of 300±5°C, a spinning speed of 2000m / min, bundling, 1.4-2 times drafting, and heat setting at 100±5°C to obtain polyester composite fibers for dust covers.
Citation Information
Patent Citations
A kind of preparation method of fluorine-containing pet-pet sheath-core composite fiber
CN103469356B
Ultraviolet-cured organic silicon / silicon dioxide hybrid super-hydrophobic fabric and preparation method thereof
CN111021043A
Preparation method of heat-resistant unsaturated polyester resin
CN111253557A
Modified hydrophobic PET sheath-core composite fiber and preparation method thereof
CN118326557A